Neurophysiological biomarkers using transcranial magnetic stimulation in Alzheimer's disease and mild cognitive impairment: A systematic review and meta-analysis. (February 2021) - Mimura, Yu; Nishida, Hana; Nakajima, Shinichiro; Tsugawa, Sakiko; Morita, Shinji; Yoshida, Kazunari; Tarumi, Ryosuke; Ogyu, Kamiyu; Wada, Masataka; Kurose, Shin; Miyazaki, Takahiro; Blumberger, Daniel M.; et al.
Highlights: TMS combined with EMG permits the generation of key neurophysiological indices in the cortex. AD patients had increased motor cortical excitability and decreased cholinergic and GABAergic functions compared with HC. MCI patients had increased motor cortical excitability and decreased cholinergic function compared with HC. TMS neurophysiology are useful measure to understand the pathophysiology of AD and MCI. Abstract: Transcranial magnetic stimulation (TMS) is a non-invasive neurophysiological tool that enables the investigation of cortical excitability in the human brain. Paired-pulse TMS paradigms include short- and long-interval intracortical inhibition (SICI/LICI), intracortical facilitation (ICF), and short-latency afferent inhibition (SAI), which can assess neurophysiological functions of GABAergic, glutamatergic, and cholinergic neural circuits, respectively. We conducted the first systematic review and meta-analysis to compare these TMS indices among patients with AD, mild cognitive impairment (MCI), and healthy controls (HC). Our meta-analyses indicated that RMT, SAI, SICI, and LICI were significantly lower in patients with AD, while ICF did not show a difference in patients with AD compared with HC. In patients with MCI, RMT and SAI were significantly lower than in HC. In conclusion, motor cortical excitability was increased, while cholinergic function was decreased in AD and MCI in comparison with HC and patients with AD had decreased GABAergic and glutamatergic functions compared with HC. Our results warrant further studies to differentiate AD, MCI, and HC, employing multimodal TMS neurophysiology.